(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
This book includes: safety and quality of fisheries products, traceability and labelling of fishery products, technical Guidlines for Responsible Fish Trade, fish trade and the Convention on International Trade in Endangered Species of Wild Fauna and Flora, harmnization of catch and trade documentation.
Keywords: Fish trade,Fisheries,Thương mại nghề cá,Thủy sản; Congresses,Tài liệu hội nghị, hội thảo